Foreign Portfolio Investment Inflows and Economic PErformance in Malaysia: A Disaggregated Analysis - Jarita Duasa; Salina Kassim (Gadjah Mada International Journal of Business, 2008)
Based on disaggregated data, this study empirically examines the importance of foreign portfolio investment (FPI) to the Malaysian economic performance. The study adopts the vector error correction model to analyze the relationships between FPI inflows from major investing countries, namely the United States, the United Kingdom, Singapore and Hong Kong and Malaysia’s real GDP using quarterly data covering the period from Q1:1991 to Q3:2007. For further inferences, this study adopts an innovation accounting by simulating variance decompositions and impulse response functions. This study finds that there is a significant positive association between Malaysia’s GDP and U.K.’s FPI inflow, particularly in the long run.